PENERAPAN MODEL KOOPERATIF TIPE SQ3R PADA MATERI TATA SURYA UNTUK MENINGKATKAN PENGUASAAN KONSEP SISWA KELAS VII SMPN 6 SIAK HULU - Exsy Martinqa; Zuhdi Ma’aruf; Zulhelmi Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : One of the problems faced in Indonesia is the weakness of the learning process where currently students are not encouraged to develop their thinking skills, and learning in class is only directed at memorizing information without being required to understand what they remember. One way that is considered to be able to overcome problems in the teaching and learning process is by applying the SQ3R cooperative model (survey, question, read, recite, review). This study aims to describe and find out the differences in students' mastery of concepts using the SQ3R cooperative model and conventional learning. The type of research used was a Quasi Experiment with a Posttest Only Design, namely using one experimental class and one control class. The sampling technique used is simple random sampling. The sample in this study were students of SMPN 6 Siak Hulu with class VII 4 as the experimental class and class VII 5 as the control class. The research data was collected by giving a test in the form of a posttest which totaled 10 questions which were analyzed descriptively and to see the increase in students' mastery of concepts using SPSS 23 as an inferential analysis. The results of the research from the descriptive and inferential analysis showed that there was a difference in the students' mastery of the concepts in the experimental class and the control class, the average score of the experimental class was higher than that of the control class. It can be concluded from this study that the SQ3R cooperative model can improve students' mastery of concepts at SMPN 6 Siak Hulu.Keywords: Concept Mastery, SQ3R Cooperative model, Solar System.